Tailoring nutrition and cancer education materials for breast cancer patients. Issue 2 (February 2022) - Melnic, Irina; Alvarado, Angelica E.; Claros, Maria; Martinez, Chanel I.; Gonzalez, Javier; Gany, Francesca
Highlights: Many immigrant breast cancer patients seen at safety net facilities are vulnerable to food insecurity. An English/Spanish nutrition presentation was developed for breast cancer patients. Iterative development involved 7 rounds of cognitive interviews per language. Changes included adapting to regional lexicons and tailoring layout and visuals. Culturally/linguistically responsive food examples and labeled images were needed. Abstract: Objective: Many breast cancer patients are vulnerable to poor nutritional status and may benefit from nutrition education, but existing materials are not generally tailored to the needs of low-literacy immigrant and minority patients. Methods: With nutritionist guidance, we developed a nutrition presentation for breast cancer patients. English- (n = 29) and Spanish-speaking (n = 19) patients were recruited from 5 safety-net hospitals, an academic cancer center, and a Latina cancer support organization. Materials were tested using multiple rounds of cognitive interviewing (with an adapted USDA interview guide), followed by study team reviews and modifications, until saturation. Results: Seven rounds of interviews per language were needed. Approximately 25% of interviewees had less than a high school education. Changes included adapting to regional lexicons and resolving vague/confusing phrasing. Specific food examples needed cultural tailoring. Text color coding (red/bad, green/good) was requested. Labeled images enhanced participants' understanding of concepts. Spanish speakers expressed a desire to understand nutrition labeling, and this was emphasized in the Spanish slides. Conclusion: Cognitive interviews were an important tool for creating a nutrition curriculum tailored to the needs of low-literacy, mostly immigrant patients. Practice implications: Cultural and linguistic factors should be considered for nutritional education materials in diverse patient populations.